Early IFNγ-Mediated and Late Perforin-Mediated Suppression of Pathogenic CD4 T Cell Responses Are Both Required for Inhibition of Demyelinating Disease by CNS-Specific Autoregulatory CD8 T Cells - Boyden, Alexander W.; Brate, Ashley A.; Karandikar, Nitin J. (Frontiers in Immunology, 2018)
Pathogenesis of immune-mediated demyelinating diseases like multiple sclerosis (MS) is thought to be governed by a complex cellular interplay between immunopathogenic and immunoregulatory responses. We have previously shown that central nervous system (CNS)-specific CD8 T cells have an unexpected protective role in the mouse model of MS, experimental autoimmune encephalomyelitis (EAE). In this study, we interrogated the suppressive potential of PLP178-191-specific CD8 T cells (PLP-CD8). Here, we show that PLP-CD8, when administered post-disease onset, rapidly ameliorated EAE progression, and suppressed PLP178-191-specific CD4 T cell responses as measured by delayed-type hypersensitivity (DTH). To accomplish DTH suppression, PLP-CD8 required differential production of perforin and IFNγ. Perforin was not required for the rapid suppressive action of these cells, but was critical for maintenance of optimal longer term DTH suppression. Conversely, IFNγ production by PLP-CD8 was necessary for swift DTH suppression, but was less significant for maintenance of longer term suppression. These data indicate that CNS-specific CD8 T cells employ an ordered regulatory mechanism program over a number of days in vivo during demyelinating disease and have mechanistic implications for this immunotherapeutic approach.